Agility and discipline made easy : practices from OpenUP and RUP - Kroll, Per (Addison-Wesley object technology series., 2006)
"The Japanese samurai Musashi wrote: 'One can win with the long sword, and one can win with the short sword. Whatever the weapon, there is a time and situation in which it is appropriate.' "Similarly, we have the long RUP and the short RUP, and all sizes in between. RUP is not a rigid, static recipe, and it evolves with the field and the practitioners, as demonstrated in this new book full of wisdom to illustrate further the liveliness of a process adopted by so many organizations around the world. Bravo!"--Philippe Kruchten, Professor, University of British Columbia "The Unified Process and its practices have had, and continue to have, a great impact on the software industry. This book is a refreshing new look at some of the principles underlying the Unified Process. It is full of practical guidance for people who want to start, or increase, their adoption of proven practices. No matter where you are today in terms of software maturity, you can start improving tomorrow."--Ivar Jacobson, Ivar Jacobson Consulting "Kroll and MacIsaac have written a must-have book. It is well organized with new principles for software development. I encounter many books I consider valuable; I consider this one indispensable, especially as it includes over 20 concrete best practices. If you are interested in making your software development shop a better one, read this book!" --Ricardo R. Garcia, President, Global Rational User Group Council, www.rational-ug.org/index.php "Agile software development is real, it works, and it's here to stay. Now is the time to come up to speed on agile best practices for the Unified Process, and this book provides a great starting point." --Scott W. Ambler, practice leader, Agile Modeling "IBM and the global economy have become increasingly dependent on software over the last decade, and our industry has evolved some discriminating best practices. Per and Bruce have captured the principles and practices of success in this concise book; a must for executives, project managers, and practitioners. These ideas are progressive, but they strike the right balance between agility and governance and will form the foundation for successful systems and software developers for a long time." --Walker Royce, Vice President, IBM Software Services-Rational "Finally, the RUP is presented in digestible, byte-size pieces. Kroll and MacIsaac effectively describe a set of practices that can be adopted in a low-ceremony, ad hoc fashion, suited to the culture of the more agile project team, while allowing them to understand how to scale their process as needed." --Dean Leffingwell, author and software business advisor and executive "This text fills an important gap in the knowledge-base of our industry: providing agile practices in the proven, scalable framework of the Unified Process. With each practice able to be throttled to the unique context of a development organization, Kroll and MacIsaac provide software teams with the ability to balance agility and discipline as appropriate for their specific needs." --Brian G. Lyons, CTO, Number Six Software, Inc. In Agility and Discipline Made Easy, Rational Unified Process (RUP) and Open Unified Process (OpenUP) experts Per Kroll and Bruce MacIsaac share twenty well-defined best practices that you and your team can start adopting today to improve the agility, predictability, speed, and cost of software development. Kroll and MacIsaac outline proven principles for software development, and supply a number of supporting practices for each. You'll learn what problems each practice addresses and how you can best leverage RUP and OpenUP (an open-source version of the Unified Process) to make the practice work for you. You'll find proactive, prescriptive guidance on how to adopt the practices with minimal risk and implement as much or as little of RUP or OpenUP as you want. Learn how to apply sample practices from the Unified Process so you can Execute your project in iterations Embrace and manage change Test your own code Describe requirements from the user perspective Architect with components and services Model key perspectives Whether you are interested in agile or disciplined development using RUP, OpenUP, or other agile processes, this book will help you reduce the anxiety and cost associated with software improvement by providing an easy, non-intrusive path toward improved results--without overwhelming you and your team.